Solubility of Hydroxytyrosol in binary mixture of ethanol + water from (293.15 to 318.15) K: Measurement, correlation, dissolution thermodynamics and preferential solvation (2020)
Hydroxytyrosol (HXT) (also known as 3,4-dihydroxyphényléthanol,) is a biophenol extracted from olive. HXT is known for its high antioxidant significance effect. In this work, we focused on the study of the behavior of the solubility of HXT in binary solvent mixtures (ethanol + water) as well as the thermodynamic proprieties. The solubility of HXT in water, ethanol and in binary solvent mixtures (ethanol + water) was measured at five different temperatures from (293.15 to 318.15) K. The enthalpy of fusion and the melting point of HXT were experimentally determined since they are essential for the study of the of solubility and crystallization process. Thermodynamic properties of dissolution of the HXT (Gibbs energy (ΔsolG°), molar enthalpy of dissolution (ΔsolH°), and molar entropy of dissolution (ΔsolS°)) are predicted using the van’t Hoff analysis, the Gibbs equation, and the measured solubilities data. The preferential solvation has been determined using the inverse Kirkwood–Buff integral (IKBI) theory.